Long-term outcomes after an initial experience of computer-navigated resection of primary pelvic and sacral bone tumours: soft-tissue margins must be adequate to reduce local recurrences. (April 2019) - Nandra, R.; Matharu, G.; Stevenson, J.; Parry, M.; Grimer, R.; Jeys, L.
Abstract : Aims: The aim of this study was to investigate the local recurrence rate at an extended follow-up in patients following navigated resection of primary pelvic and sacral tumours. Patients and Methods: This prospective cohort study comprised 23 consecutive patients (nine female, 14 male) who underwent resection of a primary pelvic or sacral tumour, using computer navigation, between 2010 and 2012. The mean age of the patients at the time of presentation was 51 years (10 to 77). The rates of local recurrence and mortality were calculated using the Kaplan–Meier method. Results: Bone resection margins were all clear and there were no bony recurrences. At a mean follow-up for all patients of 59 months (12 to 93), eight patients (34.8%) developed soft-tissue local recurrence, with a cumulative rate of local recurrence at six-years of 35.1% (95% confidence interval (CI) 19.3 to 58.1). The cumulative all-cause rate of mortality at six-years was 26.1% (95% CI 12.7 to 49.1). Conclusion: Despite the positive early experience with navigated-assisted resection, local recurrence rates remain high. With increasing knowledge of the size of soft-tissue margins required to reduce local recurrence and the close proximity of native structures in the pelvis, we advise against compromising resection to preserve function, and encourage surgeons to reduce local recurrence by prioritizing wide resection margins of the tumour. Cite this article: Bone Joint J 2019;101-B:484–490.